English Online Learning at Senior High School: Bilingual Models and Strategies - Avioleta Qory Chandra; Nurlaila Kadariyah; Hidayah Nor (ELITE JOURNAL, 2023)
This study was aimed to analyze bilingual models and strategies during the online learning in senior high school and the challenges faced by the teachers during implementing the models and strategies. The research used case study qualitative method. The data were obtained from the results of observations, interviews and documentation and they were processed through the process of data reduction, data display, drawing conclusion and verification. The participants of the research were three English teachers. The findings of this research were divided into three points. First, the bilingual model used by the English teachers during online learning was Transitional Bilingual Education (TBE). Second, the bilingual strategies used by the English teachers during online learning were metalinguistic strategies and translanguaging. Third, the challenges faced by the English teachers in implementing bilingual model and strategies during online learning were technical problem, students’ English diversity level and material complexity, and students’ passive participation in the classroom. Keywords: Bilingual Education; Model, Strategy